2019
DOI: 10.7150/jca.32339
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication and Sister Chromatid Cohesion 1 (DSCC1) of the Replication Factor Complex CTF18-RFC is Critical for Colon Cancer Cell Growth

Abstract: DNA replication and sister chromatid cohesion 1 (DSCC1) combines with chromosome transmission-fidelity protein 18 (CTF18) to form a CTF18-DSCC1-CTF8 (CTF18-1-8) module, which in combination with CTF18-replication factor C (RFC) acts as a proliferating cell nuclear antigen (PCNA) loader during DNA replication-associated processes. It was found that DSCC1 was overexpressed in tumor tissues from patients with colon cancer and that the survival probability of patients with colon cancer was lower when the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…When the cytoplasmic DSCC1 expression is higher in the tumor area, the survival probability of colon cancer patients is lower. [ 27 , 28 ] Some studies have explored DSCC1 as a potential tumor biomarker for early diagnosis and prognosis. By interfering with the function of DSCC1, proliferation and survival of tumor cells may be affected.…”
Section: Discussionmentioning
confidence: 99%
“…When the cytoplasmic DSCC1 expression is higher in the tumor area, the survival probability of colon cancer patients is lower. [ 27 , 28 ] Some studies have explored DSCC1 as a potential tumor biomarker for early diagnosis and prognosis. By interfering with the function of DSCC1, proliferation and survival of tumor cells may be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, overexpression of DSCC1 (DNA replication and sister chromatid cohesion 1) was found to increase proliferation, invasion and migration of breast carcinoma cells, as well as its knockdown showed opposite outcomes [ 43 , 44 ]. Besides, the authors found that DSCC1 could promote breast carcinoma progression by activating the Wnt/β-catenin signalling and inhibiting p53 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The role of RFC in human cancers, including CRC, has been identified. 7,9,10,[19][20][21] Although multiple pathological factors are involved in the progression of CRC, RFC regulates a range of tumor phenotypes, including proliferation, metastasis, and invasion. 7,21 Members of the RFC family are structurally and functionally similar.…”
Section: Rfc5 Knockdown Inhibits Crc Progression and May Affect The V...mentioning
confidence: 99%